2021
DOI: 10.1111/1750-3841.15716
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microwave vacuum drying on the moisture migration, microstructure, and rehydration of sea cucumber

Abstract: Effectsof microwave vacuum drying (MVD) on moisture migration, microstructure, and rehydration of sea cucumber were investigated in this paper. Vacuum condition avoided the exposure of sea cucumber to high temperature. Low‐field nuclear magnetic resonance relaxation results revealed that the peaks of three water components in sea cucumber shifted to short relaxation time during MVD process, and the peak area of major water component—immobilized water—decreased significantly due to water evaporation. Magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
12
0
2
Order By: Relevance
“…So, from the experimental results, it was observed that as the microwave power increased, the value of D eff also enhanced resulting in lessening the drying period. This could be owing to the reason that as the microwave power enhances or as the mass of the peel sample decreases a quick heating of the sample occurs, consequently raising the vapor pressure within the sample which could make the diffusion of moisture toward the surface quicker (Dak & Pareek, 2014; He et al., 2021). Also, as the value of microwave power increases, the greater amount of energy will be produced by the liberation of heat.…”
Section: Resultsmentioning
confidence: 99%
“…So, from the experimental results, it was observed that as the microwave power increased, the value of D eff also enhanced resulting in lessening the drying period. This could be owing to the reason that as the microwave power enhances or as the mass of the peel sample decreases a quick heating of the sample occurs, consequently raising the vapor pressure within the sample which could make the diffusion of moisture toward the surface quicker (Dak & Pareek, 2014; He et al., 2021). Also, as the value of microwave power increases, the greater amount of energy will be produced by the liberation of heat.…”
Section: Resultsmentioning
confidence: 99%
“…The values of fragility and hardness of papaya slices under different drying parameters were listed in Table 3, showing an upward trend with the increase of thickness. This might be interpreted as the moisture migration process that drove the sugar inside the material to accumulate on the surface, forming the crust structure on the surface (He et al, 2021). The thicker the papaya slices, the longer path of moisture migration and more obvious crusts.…”
Section: Resultsmentioning
confidence: 99%
“…This might be because the increase in power density caused excessive dehydration within a short time and the cell structure inside the papaya slice be damaged, resulting in the growth of hardness value. Some researchers also found that the hardness value was added with the increase of microwave power density during microwave vacuum drying (He et al, 2021; Manish Dak et al, 2014). There is no significant difference ( p > .05) in the fragility and hardness of papaya at different drying temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, a large volume of 3% sodium chloride is employed in saline, leading to environmental pollution, resource waste, time consumption and seasonal dependence (Tamarit‐Pino et al ., 2019). The rehydration properties, thermal‐induced degradation and active compound loss of solar‐salted sea cucumbers is significantly affected by a series of complex treatments (Tamarit‐Pino et al ., 2020; He et al ., 2021). Therefore, low‐temperature and high‐efficiency drying methods, such as hot‐air drying, hot‐pump drying, vacuum oven‐drying, far‐infrared radiation drying, microwave drying and freeze‐drying, have been used to shorten the processing time and improve product quality (Duan et al ., 2010, 2007; Moon et al ., 2014; Ridhowati et al ., 2018; Shamsuddeen et al ., 2021).…”
Section: Thermal Treatment Methods For Sea Cucumbersmentioning
confidence: 99%
“…Therefore, low‐temperature and high‐efficiency drying methods, such as hot‐air drying, hot‐pump drying, vacuum oven‐drying, far‐infrared radiation drying, microwave drying and freeze‐drying, have been used to shorten the processing time and improve product quality (Duan et al ., 2010, 2007; Moon et al ., 2014; Ridhowati et al ., 2018; Shamsuddeen et al ., 2021). Several drying treatments have been combined, including microwave vacuum drying (MVD) (He et al ., 2021), vacuum freeze‐drying (Bai & Luan, 2018) and hybrid heat pump vacuum drying (Shamsuddeen et al ., 2021). For instance, using high microwave power (200 or 250 W) in MVD accelerated the evaporation of water from the interior layer of the sea cucumber body wall to the exterior layer, which generated a porous microstructure that contributed to faster rehydration.…”
Section: Thermal Treatment Methods For Sea Cucumbersmentioning
confidence: 99%